Effect of environmental factors and fishing effort allocation on catch of the Spotted Eagle Ray Aetobatus narinari (Rajiformes: Myliobatidae) in Southern Gulf of Mexico - Cuevas, Elizabeth (2013)
Aetobatus narinari represents a fisheries target in Southern Gulf of Mexico, and it is currently considered a Near Threatened species by the IUCN red list. The information available of this batoid fish includes some biological and fishery aspects; nevertheless, little is known about the factors influencing on fishing operations and catches. In order to evaluate the effect of environmental factors and the fishing effort allocation by vessels on the target fishery of A. narinari in this area, a daily basis sampling was carried out on four small-scale vessels, from January to July 2009 (the entire fishing season), in two fishing localities (Campeche and Seybaplaya). A total of 896 rays were recorded from 280 fishing trips. A General Linear Model was used to predict the factors effect on the probability that fishing operations occurred, and on the probability for captures of at least one or three or five rays per vessel-trip. The probability that fishing operations occurred off Campeche was predicted by the lunar cycle, with the highest probability in the new moon period (66%) and a probability smaller than 35% for the other periods. The probability that fishing operations occurred off Seybaplaya was predicted by wind velocity, with higher probabilities at low wind velocity than at high wind velocity, and a 50% probability of fishing operations at 12-15km/h. Catch rates off Seybaplaya were predicted by the vessel´s factor (the effect of fishing effort allocation), the North wind season and sea surface temperature. The probability for captures of at least one and three rays per vessel-trip was predicted by the vessel´s factor and the North wind season. One vessel had higher catch probability (83% for at least one ray and 43% for at least three rays) than the others (69 and 70% for at least one ray and 26% for at least three rays), and during the North wind season the catch probability was higher (96% for at least one ray and 72% for at least three rays) than out of that season (68% for at least one ray and 21% for at least three rays). The probability for capture at least five rays per vessel-trip was predicted by the sea surface temperature and the North wind season. At 23°C the catch probability was of 49% and the probability gradually diminished to 4% at 28°C, and during the North wind season the catch probability was higher (40%) than out of that season (7%). This study shows that some environmental factors and fishermen perceptions and experience (fishing effort allocation) influence on the catch rate of A. narinari, and that these factors must be considered in future studies on elasmobranch fisheries, mainly when comparisons between catch rates among seasons or regions are analyzed.